PENGARUH KETINGGIAN LUBANG UDARA PADA TUNGKU PEMBAKARAN BIOMASSA TERHADAP UNJUK KERJANYA - Arif Mulyanto; Mirmanto Mirmanto; Muhammad Athar (Universitas Mataram, 2016)
Alternative energies, e.g. biomassa, can be utilized using combustion processes in a stove. Nevertheless, traditional stoves that are available in the market or have been used by the community for years are not effective and efficient. One thing that may affect their efficiency and effectiveness is a distance between the combustion chamber and air hole. Therefore, this research investigates experimentally the effect of the distance.The tested stoves had identical combustion room and air hole diameters, but the distance between the combustion chamber and air hole was varied 10 cm, 20 cm, 30 cm, 40 cm. The combustion chamber diameter was 13 cm and the top diameter of the stove was 19 cm. The fuel employed was coconut shell with various size of 2-4 cm and 5-10 cm. One traditional stove was also tested as a comparison. The test were conducted by heating the water in a 18 cm diameter pan from the ambient temperature to the boiling temperature (1000C). Investigated parameters showing the stove performance were boiling time, FCR, heat input, heat output, heat losses and efficiency.The results show that the fastest boiling time (472 s) and the highest FCR (0,9407 Kg/h) were resulted in the stove with the air hole distance of 40 cm and coconut shell size of 5-10 cm. In this stove, the highest heat input, heat output, heat losses occurred too. On the other hand, the highest efficiency (15,62 %) was achieved in the stove with the air hole distance of 10 cm.